Technical Innovations and their Relations with Social and Institutional In the North of Minas:: Experiences with Family Farmers in Rio Pardo de Minas, MG - Correia, João Roberto; Lima, Herbert Cavalcante de (Sustainability in Debate, 2015)
This article explores the relation among technical, social and institutional innovations of family farming communities (geraizeiros) in northern Minas Gerais State, Brazil, in order to create a dialogue with knowledge construction processes. This work confirms the existence of a strong correlation between the above-mentioned aspects of innovations. Possibly, the observed situation is related to recent acquired knowledge and to its integration with farmers’ own social relations, which are directly connected to nature. Technological innovations created by geraizeiros are the product of social and institucional innovations.